100 Hz Electroacupuncture Alleviated Chronic Itch and GRPR Expression Through Activation of Kappa Opioid Receptors in Spinal Dorsal Horn - Li, Hong-Ping; Wang, Xiao-Yu; Chen, Chao; Li, Jing-Jing; Yu, Chi; Lin, Li-Xue; Yu, Zi-E; Jin, Zhi-Yuan; Zhu, He; Xiang, Hong-Chun; Hu, Xue-Fei; Cao, Jie; et al. (Frontiers in Neuroscience, 2021)
Background: Clinical studies have shown that electroacupuncture (EA) alleviates chronic itch. Gastrin releasing peptide receptor (GRPR) and dynorphin (DYN) in spinal dorsal horn positively or negatively regulate itch respectively. However, which frequency of EA is effective on relieving chronic itch and reducing the expression of GRPR, whether DYN-A in spinal cord are involved in the underlying mechanism of anti-pruritus effect of EA remains unknown. Methods: The mixture of acetone and diethyl ether (1:1) (designated as AEW (acetone/diethyl ether and water) treatment) was used to induce dry skin model of chronic itch. EA was applied to Quchi (LI11) and Hegu (LI4). Western blot was used to detect the expression of GRPR and DYN-A. Immunofluorescence were used to detect the expression of DYN-A. Results: The AEW administration induced remarkable spontaneous scratching, enhanced the expression of GRPR and reduced the expression of DYN-A. Compared with sham EA group, 2 Hz or 15 Hz EA group, 100 Hz EA was the most effective frequency on relieving chronic itch, reducing the expression of GRPR and increasing the expression of DYN-A in cervical dorsal horn. Furthermore, intraperitoneal injection of Kappa opioid receptors (KOR) antagonist nor Binaltorphimine dihydrochloride (nor-BNI) significantly reversed the effect of 100 Hz EA on the inhibition of both itching behavior and GRPR expression. Conclusions: EA at 100 Hz is the most effective frequency that inhibits chronic itch and GRPR expression through activation of Kappa opioid receptors in spinal dorsal horn, which can effectively guide the clinical treatment and improve the antipruritic effect of acupuncture.